2015
DOI: 10.3748/wjg.v21.i43.12261
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt signaling pathway in gastric carcinoma: A reality for personalized medicine?

Abstract: Frequent activation of phosphatidylinositol-3 kinases (PI3K)/Akt/mTOR signaling pathway in gastric cancer (GC) is gaining immense popularity with identification of mutations and/or amplifications of PIK3CA gene or loss of function of PTEN, a tumor suppressor protein, to name a few; both playing a crucial role in regulating this pathway. These aberrations result in dysregulation of this pathway eventually leading to gastric oncogenesis, hence, there is a need for targeted therapy for more effective anticancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 112 publications
5
96
1
1
Order By: Relevance
“…Molecular alterations of this pathway have been widely reported in cancers, which mainly include phosphorylation of PI3K and/or AKT . These molecules in the PI3K/AKT pathway regulate various physiological functions, including cell survival, proliferation, migration, invasion and protein translation . In the present study we found that the levels of p‐PI3K and p‐AKT were markedly reduced after KYNU was silenced.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Molecular alterations of this pathway have been widely reported in cancers, which mainly include phosphorylation of PI3K and/or AKT . These molecules in the PI3K/AKT pathway regulate various physiological functions, including cell survival, proliferation, migration, invasion and protein translation . In the present study we found that the levels of p‐PI3K and p‐AKT were markedly reduced after KYNU was silenced.…”
Section: Discussionsupporting
confidence: 60%
“…17 These molecules in the PI3K/AKT pathway regulate various physiological functions, including cell survival, proliferation, migration, invasion and protein translation. 20,21 In the present study we found that the levels of p-PI3K and p-AKT were markedly reduced after KYNU was silenced. We therefore suggest that KYNU possibly acts as a promoter in the growth and motility of cSCC cells, at least partially by activating the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 56%
“…demonstrated that RES reversed MDR in human breast cancer doxorubicin‐resistant cells . In the present study, we validated the assumption that RES reversed DOX resistance in breast neoplasm through inhibiting PI3K/Akt/mTOR signaling pathway, in which PI3K phosphorylated Akt, then Akt stimulated mTOR, and thus resulted in ribosomal S6 kinase (p70S6K) phosphorylation . On the other hand, the down‐regulation of caspase‐3 and inactivation of caspase‐based apoptosis was measured by western blotting and Flow Cytometry Method (FCM).…”
Section: Discussionsupporting
confidence: 76%
“…Several signaling pathways, including the wnt/β-catenin, Notch, and PI3K/Akt pathways, have been found to be aberrantly activated and play vital roles in the development and progression of gastric cancer [11, 30, 31] Among these pathways, the functions of wnt/β-catenin signaling in gastric cancer development and progression have been well documented. TCF4 and coactivator β-catenin are two key downstream effectors of the wnt/β-catenin signaling pathway, and considered as potent oncogenes in tumor progression [7].…”
Section: Discussionmentioning
confidence: 99%